An inventory of the Pteridophytic flora of Balpakram-Baghmara Landscape (BBL), South Garo Hills, Meghalaya, India - Dilip Kumar Roy; Jintu Sarma (Mongolian Journal of Biological Sciences)
In the present study the Pteridophytic flora of Balpakram-Baghmara Landscape (BBL) of South Garo Hill district, Meghalaya (India) is systematically inventoried containing 76 taxa belong to 44 genera under 22 families. Out of this 76 species, seven species namely Asplenium filipes Copel., Bolbitis aspleniifolia (Bory) K. Iwats., Dicranopteris taiwanensis Ching & P.S. Chiu, Pleocnemia submembranacea (Hyata) Tagawa & K. Iwats., Polystichum pseudotsus-simense Ching, Pteris camerooniana Kuhn, Thelypteris caudipinna Ching, and Trichomanes campanulatum Roxb. are recorded as new additions to the flora of Meghalaya. Moreover, nine species namely Bolbitis nodiflora Fraser-Jenk., Cephalomanes javanicum (Blume) Bosch, Cyathea andersoni (Scoot ex Bedd.) Copel., Dipteris wallichii (R. Br.) G. Moore, Helminthostachys zeylanica (L.) Hook., Hymenophyllum denticulatum Sw., Lindsaea himalaica K.U. Kramer, Pleocnemia submembranacea (Hyata) Tagawa & K. Iwats. and Pteris quadriaurita Retz. fall under different conservation status. The current accepted name of each species is provided here along with author citation, publication reference, basionym (if any), distribution details in North East India and conservation status (if relevant).